EMOTIONAL INTELLIGENCE ON LEADER BEHAVIOUR IMPACT ON ORGANIZATIONAL PERFORMANCE AND ENHANCING PRODUCTIVE OUTCOMES - M Nandakisore; P Muralikrishna (International Journal of Advances in Business and Management Research (IJABMR), 2025)
High-level intelligence leaders are superior to others in a positive working environment, with better interpersonal relations and better teamwork performance, all of which contributes in organizational success. This tabloid takes a critical look at the constituents and highlights their positive nexus with leadership types, specifically transformational and transactional leadership. Secondly, emotionally intelligent leaders and their influences on job satisfaction, engagement, and the overall well-being of employees are studied. Organizational performance depends not just on such technical skills but also on how leaders handle emotional climates, deal with conflicts, and inspire teams to work toward common goals. In addition, the study emphasises EI benefits decision-making, stress control, and conflict resolution, which brings/leads to better organizational consequences. Examining the complementarity between EI and leadership behaviour, the paper suggests that leaders that develop their emotional intelligence can stimulate performance improvements, innovation and long-term organisation survival. For practical theoretical findings, this means that corporations should include and prioritise the development of EI in their leadership development to take full advantage of their leaders and aspects of their organisations.